ACCOUNTING FOR POST RETIREMENT BENEFIT: EARLY ADOPTERS OF EPF - B, NAINAR (International Journal of Psychosocial Rehabilitation, 2020)
This manuscript reviews the modern situation of the Employment Provident Fund annuity classification. TheIndian understanding may perhapspotentially authority strategy decisions in additional mounting countries, more than ever those with comparabledependence on the public provident account arrangement. Institutional facial appearance of an assortment of giving up work benefitschemes isdecorated and their deficiencies are discussed. It is argued that little treatment echelon,underneathroutine of provident finance schemes due to outlay limitations, and economicdifficulty in administering unfunded community annuity programs have rendered the present classificationunsuccessful and untenable. The disastrous experiments with improvised shake-up initiatives in currentprecedent additionallay emphasis on the need for a structural and lasting modify. The manuscript concludes with some course of action instructions for reforming the OLD AGE PENSIONannuity classification.